Description of the Incident of Fever and Local Pain Following Pentabio Immunization in Infants at the Integrated Health Post (Posyandu) at the Timpah Community Health Center, Central Kalimantan - Fanita Oktavia; Rani Safitri (Jurnal Siti Rufaidah, 2025)
Immunization is a vital public health strategy to prevent infectious diseases and reduce morbidity and mortality. In Indonesia, the Pentabio vaccine protects against diphtheria, pertussis, tetanus, hepatitis B, and Haemophilus influenzae type b. Despite its effectiveness, post-immunization reactions such as fever and local pain are common, potentially affecting caregiver perceptions and immunization adherence. A descriptive observational study with a cross-sectional design was conducted among infants receiving Pentabio immunization at Posyandu in the UPT Timpah Community Health Center, Central Kalimantan. Data were collected through structured observation and caregiver interviews for infants aged 2–11 months. Fever (≥37.5°C) and local pain (tenderness, redness, or swelling) were assessed. Of the 30 infants, 40% were aged 2–3 months, 33.33% were 4–6 months, and 26.67% were 7–11 months, with slightly more males (53.33%). Post-immunization fever occurred in 60%, and local pain in 70%, with both reactions being mild, transient, and appearing within 24–48 hours. These findings highlight the commonality of mild adverse events, especially in early infancy, and underscore the need for clear caregiver education to maintain confidence in immunization services and ensure adherence to vaccination schedules.